GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 3336 species occurrences available in GBIF matching the query: TaxonKey: 2969431 HasCoordinate: true. The dataset includes 3336 records from 146 constituent datasets: 5 records from Australian National Herbarium (CANB). 1 records from SMDB - Santa Maria Departamento de Biologia. 4 records from NSW herbarium collection. 22 records from IPA - Herbário - IPA Dárdano de Andrade Lima. 54 records from PRECIS. 1 records from Botany (UPS). 1 records from IAC - Herbário do Instituto Agronômico de Campinas. 97 records from Naturalis Biodiversity Center (NL) - Botany Leiden. 33 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. 3 records from Royal Botanic Garden Edinburgh Herbarium (E). 90 records from Caracterización del hábitat de poblaciones silvestres de chigüiros (Hydrochoerus hydrochaeris) en Paz de Ariporo, Casanare. 9 records from Dieta y preferencias alimenticias de poblaciones silvestres de chigüiros (Hydrochoerus hydrochaeris) en Paz de Ariporo, Casanare. 5 records from Instituto de ciencias naturales. 2 records from Lista florística preliminar de Tamaulipas. 3 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 1 records from Herbario de la Universidad Industrial de Santander. 17 records from Herbier CNRST/INERA. 18 records from Geneva Herbarium – General Collection (G). 67 records from Especímenes INBio. 145 records from Herbario XAL del Instituto de Ecología, A.C., México (IE-XAL). 591 records from Missouri Botanical Garden. 1 records from Caracterización florística de las ciénagas en Gamarra y Barrancabermeja de 2012. 8 records from JPB - Herbário Lauro Pires Xavier. 26 records from Flora vascular acuática de la cuenca del Río Tamesí. 1 records from Inventario florístico de la región Calakmul-parte baja de la región Lacandona (Cuenca alta del Usumacinta y Marqués de Comillas). 5 records from MOSS - Herbário Dárdano de Andrade Lima. 1 records from MEXU/Flora de Oaxaca. 1 records from Carnet en Ligne. 53 records from Instituto de Botánica Darwinion. 4 records from PEUFR - Herbário Professor Vasconcelos Sobrinho. 8 records from PRECIS (KwaZulu-Natal Herbarium). 8 records from ICN - Herbário do Instituto de Ciências Naturais. 31 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 37 records from Herbario IEB del Instituto de Ecología, A.C., México (IE-BAJíO). 1 records from Herbarium Senckenbergianum (FR). 44 records from MBM - Herbário do Museu Botânico Municipal. 6 records from Caracterizaciones rápidas de biodiversidad en grupos biológicos de la planicie del valle del río Cauca. 3 records from Herbier National de Mauritanie (HNM). 1 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 3 records from iNaturalist research-grade observations. 12 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 21 records from ALCB - Herbário Alexandre Leal Costa. 1 records from naturgucker. 2 records from Herbario virtual bosques secos de Colombia - sección herbario FMB (IAvH). 2 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 18 records from The AAU Herbarium Database. 2 records from HST - Herbário Sérgio Tavares. 4 records from Herbarium togoense. 6 records from Fauna y flora asociada a 18 humedales del valle geográfico del río Cauca. 13 records from Herbier de la Guyane. 3 records from CAS Botany (BOT). 3 records from SINGER Coordinator. 1 records from Fairchild Tropical Botanic Garden Virtual Herbarium Darwin Core format. 2 records from HCF - Herbário da Universidade Tecnológica Federal do Paraná Campus Campo Mourão. 3 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 1 records from Inventario florístico de la Frailescana (zona focal), Chiapas, México. 12 records from UB - Herbário da Universidade de Brasília. 3 records from UFP - Herbário UFP - Geraldo Mariz. 3 records from Plantae, TAIF (Taiwan e-Learning and Digital Archives Program, TELDAP). 1 records from Bernice P. Bishop Museum. 36 records from Flora acuática vascular y de zonas inundables del área de protección de flora y fauna Laguna de Términos, Campeche, México. 2 records from ESA - Herbário da Escola Superior de Agricultura Luiz de Queiroz. 7 records from Catálogo y base de datos preliminar de la flora de Sinaloa. 1 records from Herbarium Specimen of the Institute of Traditional Medicine, Tanzania. 59 records from herbario. 1 records from Herbarium de Geo. B. Hinton, México. 24 records from HVASF - Herbário Vale do São Francisco. 2 records from HERBAM - Herbário da Amazônia Meridional. 1 records from Herbario virtual bosques secos de Colombia - Sección herbario TOLI (UT). 2 records from Colección Herbario Federico Medem Bogotá - FMB. 79 records from MEXU/Colección de Plantas Acuáticas. 1 records from FURB - Herbário Dr. Roberto Miguel Klein. 2 records from Colecciones de George Boole Hinton depositadas en el herbario de Kew: Familia Leguminosae. 176 records from Naturalis Biodiversity Center (NL) - Botany. 11 records from Naturalis Biodiversity Center (NL) - Botany Utrecht. 15 records from Herbarium of The New York Botanical Garden. 9 records from Herbier Ecole de Faune. 1 records from Herbarium - Las Cruces Biological Station. 2 records from CPAP - Herbário CPAP. 8 records from MAC - Herbário do Instituto do Meio Ambiente do Estado de Alagoas. 1 records from EAFM - Herbário do Instituto Federal de Educação, Ciência e Tecnologia do Amazonas. 24 records from ASE - Herbário da Universidade Federal de Sergipe. 23 records from EAC - Herbário Prisco Bezerra. 8 records from Geographically tagged INSDC sequences. 3 records from Colecta botánica: área maya región de la Reserva Calakmul, Campeche. 3 records from MFS - Herbário Profª. Drª. Marlene Freitas da Silva. 2 records from FUEL - Herbário da Universidade Estadual de Londrina. 42 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 49 records from IICT Herbário LISC. 278 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 13 records from Instituto de Ciencias Naturales. 6 records from Flora de la reserva de la biósfera de los Pantanos de Centla, en el estado de Tabasco, México. 21 records from CGMS - Herbário da Fundação Universidade Federal de Mato Grosso do Sul. 6 records from HUEM - Herbário da Universidade Estadual de Maringá. 2 records from SPF - Herbário da Universidade de São Paulo. 157 records from Naturalis Biodiversity Center (NL) - Botany Wageningen. 5 records from CEN - Herbário da Embrapa Recursos Genéticos e Biotecnologia. 8 records from BHCB - Herbário da Universidade Federal de Minas Gerais. 17 records from Flora vascular de las llanuras aluviales del bajo río Nechí. 2 records from Phanerogamic Botanical Collections (S). 49 records from Australia's Virtual Herbarium. 5 records from NMNH occurrence DwC-A. 1 records from Digital Florula - Palo Verde Biological Station. 6 records from Caracterización de fauna y flora para el establecimiento de límites funcionales de humedales en tres ventanas piloto: Ciénaga de la Virgen, Ciénaga Zapatosa y Complejo de humedales Paz de Ariporo - Hato Corozal. 1 records from Herbario de Plantas Vasculares de la Universidad de Salamanca: SALA. 4 records from MBML-Herbario - Herbário Mello Leitão. 1 records from UA Herbarium. 1 records from HCDAL - Herbário Caririense Dárdano de Andrade-Lima. 97 records from Flora Atlas N.T.. 6 records from West-, Central- and East African Plants Databases. 8 records from R - Herbário do Museu Nacional. 4 records from Natural History Museum (London) Collection Specimens. 4 records from TEPB - Herbário Graziela Barroso. 17 records from Herbario Amazónico Colombiano. 12 records from Colección del Herbario de la Universidad Tecnológica del Chocó. 1 records from Marie-Victorin Herbarium (MT). 2 records from Herbier du Bénin. 11 records from CESJ - Herbário Leopoldo Krieger. 1 records from Caracterización de la vegetación en los sectores de Aipe (Huila), Yaví (Tolima) y Dagua (Valle del Cauca), como insumo para la identificación de oportunidades de conservación y la recuperación de servicios ecosistémicos del bosque seco. 33 records from Field Museum of Natural History (Botany) Seed Plant Collection. 1 records from Phanérogames recensés aux Monts Nimba. 68 records from Vascular plants collection (P) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1 records from OUPR - Herbário "Professor José Badini". 3 records from The System-wide Information Network for Genetic Resources (SINGER). 18 records from Herbario Universidad de Antioquia (HUA). 2 records from HUFSJ - Herbário da Universidade Federal de São João del-Rei. 19 records from University of Ghana - Ghana Herbarium. 1 records from HUTO - Herbário da Universidade de Tocantins. 4 records from Plants of Papua New Guinea. 45 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 1 records from IRAI - Herbário do Parque da Ciência Newton Freire Maia. 162 records from Nationaal Herbarium Nederland. 6 records from HAMAB - Herbário Amapaense. 3 records from Herbarium of Taiwan Forestry Research Institute. 1 records from DVPR - Herbário da Universidade Tecnológica Federal do Paraná - Dois Vizinhos. 15 records from Formación del banco de datos del herbario (UCAM). 8 records from Composición florística del Parque Nacional Huatulco. 10 records from Census of the flora of Benin. 14 records from Flora acuática vascular del área focal Felipe Carrillo Puerto, Corredor Biológico Sian Ka'an-Calakmul, Quintana Roo, México. 3 records from Herbarium (UNA). 1 records from HUESB - Herbário da Universidade Estadual do Sudoeste da Bahia. 9 records from CEPEC - Herbário do Centro de Pesquisas do Cacau. 8 records from HTSA - Herbário do Trópico Semiárido. 23 records from UEC - Herbário da Universidade Estadual de Campinas. 2 records from VIES - Herbário Central da Universidade Federal do Espírito Santo. 11 records from VIC - Herbário da Universidade Federal de Viçosa.
Keywords: GBIF; biodiversity; species occurrences